18th century droughts in Portugal - Fragoso, M. (2018)
Droughts are meteorological extreme events that have significant impacts on individuals and societies. Records of their impacts and/or measures taken to avoid them have been retrieved from different documentary sources in the frame of the KlimHist Project. The database constructed within this project gathers more than 3000 entries which permit to reconstruct different extreme weather events. Individual sources, including memoirs, books, poems and newspaper articles and institutional sources including civil and ecclesiastical sources are used. In this presentation we present evidence of 18th century droughts which occurred in two Portuguese regions: NW Portugal (data mostly from Oporto and Braga) and “Central Portugal”, (e.g. the area between Lisbon and Évora). Evidence refers to water scarcity (mainly due to low rainfall amounts), insufficient water resources (and low river flows), as well as consequences of lack of water in agriculture, animal husbandry, economy, health and mortality rates. The main drought periods occurred in 1714-15, 1734-38, 1750-57 and 1779-83. Some significant drought episodes will be reconstructed in detail, mainly those when pro-pluvia ceremonies took place. Most droughts occurred in spring, winter and summer, although there are regional differences: NW Portugal is mostly associated with summer droughts whilst Central Portugal (where it hardly ever rains in summer) attracts with spring and winter droughts.